2020
DOI: 10.1016/j.ijpsycho.2020.09.017
|View full text |Cite
|
Sign up to set email alerts
|

From adaptive to maladaptive fear: Heterogeneity in threat and safety learning across response systems in a representative sample

Abstract: Individual differences in fear learning are a crucial prerequisite for the translational value of the fearconditioning model. In a representative sample (N = 936), we used latent class growth models to detect individual differences in associative fear learning. For a series of subsequent test phases varying in ambiguity (i.e., acquisition, extinction, generalization, reinstatement, and re-extinction), conditioned responding was assessed on three response domains (i.e., subjective distress, startle responding, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 77 publications
0
18
0
Order By: Relevance
“…Though Gazendam et al (2020) did not report any subgroups with an overall decrease in differential responding during acquisition, analysis of mean responding during each trial revealed that danger cue responding was beginning to decrease by the end of acquisition for three of five subgroups. Of note, the fear learning paradigm used by Gazendam et al (2020) included a total of six danger cue trials during acquisition. A longer acquisition period may have led to an overall decrease in differential fear responding during acquisition in some participants.…”
mentioning
confidence: 66%
See 4 more Smart Citations
“…Though Gazendam et al (2020) did not report any subgroups with an overall decrease in differential responding during acquisition, analysis of mean responding during each trial revealed that danger cue responding was beginning to decrease by the end of acquisition for three of five subgroups. Of note, the fear learning paradigm used by Gazendam et al (2020) included a total of six danger cue trials during acquisition. A longer acquisition period may have led to an overall decrease in differential fear responding during acquisition in some participants.…”
mentioning
confidence: 66%
“…However, mean comparisons of LCGA-derived extinction subgroups revealed substantial differences in the rate of FPS increase during acquisition, leading to a more than fivefold difference in FPS between Modal FPS Responders and the two other classes at the beginning of extinction (Galatzer-Levy et al, 2017). Though Gazendam et al (2020) did not report any subgroups with an overall decrease in differential responding during acquisition, analysis of mean responding during each trial revealed that danger cue responding was beginning to decrease by the end of acquisition for three of five subgroups. Of note, the fear learning paradigm used by Gazendam et al (2020) included a total of six danger cue trials during acquisition.…”
mentioning
confidence: 95%
See 3 more Smart Citations